Translating Ribosome Affinity Purification (TRAP) to Investigate Arabidopsis thaliana Root Development at a Cell Type-Specific Scale - Thellmann, Martha; Grube Andersen, Toni; Vermeer, Joop (My University, 2020)
In this article, we give hands-on instructions to obtain translatome data from different Arabidopsis thaliana root cell types via the translating ribosome affinity purification (TRAP) method and consecutive optimized low-input library preparation. As starting material, we employ plant lines that express GFP-tagged ribosomal protein RPL18 in a cell type-specific manner by use of adequate promoters. Prior to immunopurification and RNA extraction, the tissue is snap frozen, which preserves tissue integrity and simultaneously allows execution of time series studies with high temporal resolution. Notably, cell wall structures remain intact, which is a major drawback in alternative procedures such as fluorescence-activated cell sorting-based approaches that rely on tissue protoplasting to isolate distinct cell populations. Additionally, no tissue fixation is necessary as in laser capture microdissection-based techniques, which allows high-quality RNA to be obtained. However, sampling from subpopulations of cells and only isolating polysome-associated RNA severely limits RNA yields. It is, therefore, necessary to apply sufficiently sensitive library preparation methods for successful data acquisition by RNA-seq. TRAP offers an ideal tool for plant research as many developmental processes involve cell wall-related and mechanical signaling pathways. The use of promoters to target specific cell populations is bridging the gap between organ and single-cell level that in turn suffer from little resolution or very high costs. Here, we apply TRAP to study cell-cell communication in lateral root formation.